Divergent impacts of soil desiccation on atmospheric water vapor–temperature responses regulated by evapotranspiration - Ruonan Wang; Xingwang Fan; Yongwei Liu; Xiaosong Zhao; Rong Wang; Yuanbo Liu (Environmental Research Letters)
Climate warming induces temporally varying atmospheric water vapor (WV), yet the spatial distribution of opposing trends across global land remains elusive. Here, we use the monthly European Centre for Medium-range Weather Forecasts Reanalysis v5 dataset to discern the responses of WV changes to the rising air temperature from 1982 to 2020. Simultaneous increases in both the WV and air temperature are observed over approximately three-quarters of global land, with a median of 0.21 mm·K ^–1 , particularly evident in the tropics. Strong positive responses are primarily influenced by increasing trends in evapotranspiration (ET) and low-elevation areas. About one-fifth of global land shows a decline in WV with a median of −0.62 mm·K ^–1 , predominantly in southeastern South America and southwestern North America. Negative responses are also driven by ET trends, where strong ET enhances these effects that are less pronounced in high-altitude regions. The prevalence of a positive response is highest during September–October–November (81%), while a negative response was observed most in December–January–February (35%). The spatial distribution of negative responses generally aligns with soil desiccation patterns; soil desiccation exacerbates negative responses in humid regions due to evaporative cooling but mitigates them in arid regions due to intensified warming. This study enhances our comprehension regarding the divergent responses of atmospheric WV toward global warming.